Analysis of wild boar‐domestic pig interface in Europe: spatial overlapping and fine resolution approach in several countries. Issue 1 (6th January 2021) - ; Illanas, Sonia; Fernández‐López, Javier; Acevedo, Pelayo; Apollonio, Marco; Blanco‐Aguiar, Jose Antonio; Brivio, Francesca; Croft, Simon; Ferroglio, Ezio; Keuling, Oliver; Plis, Kamila; Podgórski, Tomasz; et al.
Abstract : In order to define the spatial interface between wild boar and domestic pigs in Europe, the ENETWILD consortium (www.enetwild.com ) described in a preliminary report the different sources of data for domestic pigs at European scale, and developed a preliminary risk map of possible spatial interaction between both groups. This modelexplored and assessed the use of pig distribution data from Gridded Livestock of the Worlddatabase (GLW), FAO. However, in some specific countries used as cases, the GLW predictions did not reliably represent the pig abundance distribution within countries. The currently available census data of livestock at the European Union level (Eurostat) is limited to the spatial resolution at NUTS2. While Eurostat ensures that data can be potentially comparable, there is still needed to resolve definition issues regarding better spatial resolution (level of aggregation of information) and the pig production systems. In this context, the objectives of this report are (i) assessing the spatial interface between pigs and wild boar over Europe using the best quality data available (Eurostat data and ENETWILD spatial models). We(ii) secondly assessed the interface at higher spatial resolution, distinguishing pig production types in countries where data was available. Based on comparisons at different scales and quality of data, we propose future steps in both data collection and modelling approach.Precisespatial resolution of pig data is not available at European level yet, and the discrimination of extensive vs . intensive farms, backyards vs . commercial; outdoor vs . indoor, is essential to quantify and perform risk analyses separatelyfor each production system and/or considering this relevant source of variation in risk at the interface. The development of a framework to collect harmonised and standardised data at European scale athigher resolution is needed.